Pulping yield and delignification kinetics of heartwood and sapwood of maritime pine - Esteves, Bruno (2021)
In maritime pine (Pinus pinaster Ait.), heartwood represents a substantial part of the tree stem at final harvest age (80 years) corresponding to 42% at the base of the stem wood diameter and decreasing upward. The rate of heartwood formation was estimated at 0.35 rings/year, beginning at 18 years of age. Differences in the chemical composition between heartwood and sapwood were mainly in the extractives, 19.7% and 5.8%, respectively. The lignin content was 23.1% and 24.5% in the heartwood and sapwood, respectively. Pulping yield of the heartwood was lower than that of the sapwood (40.0% vs. 49.7%) and was negatively correlated with the extractives content. Extraction of heartwood prior to pulping increased the pulp yield and the delignification (lower residual lignin in pulps). Pulping kinetics showed lower yields for heartwood at all pulping stages, the difference occurring especially in the initial reaction phase. However, delignification rate constants were similar for heartwood and sapwood (3.1 1022 min21 and 2.7 1022 min21 for the main delignification phase for sapwood and heartwood, respectively), with a lower activation energy for sapwood (68.3 vs. 90.0kJ.mol21). The presence of heartwood decreases the raw-material quality for pulping and this should be taken into account when harvesting trees for pulping processes.